2015
DOI: 10.1051/0004-6361/201425509
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances of giant stars in NGC 5053 and NGC 5634, two globular clusters associated with the Sagittarius dwarf spheroidal galaxy?

Abstract: Context. The tidal disruption of the Sagittarius dwarf spheroidal galaxy (Sgr dSph) is producing the most prominent substructure in the Milky Way (MW) halo, the Sagittarius Stream. Aside from field stars, it is suspected that the Sgr dSph has lost a number of globular clusters (GC). Many Galactic GC are thought to have originated in the Sgr dSph. While for some candidates an origin in the Sgr dSph has been confirmed owing to chemical similarities, others exist whose chemical composition has never been investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 83 publications
2
49
1
Order By: Relevance
“…Among the most likely members, only NGC 5634 and Whiting 1 are far away from the Sgr core and both are associated with the trailing arm in the LM10 model. Although no underlying population was found at a compatible distance around NGC 5634 in CB14, the abundances derived by Sbordone et al (2015) for this cluster are consistent with those of the main body of Sgr. Law & Majewski (2010a) also show that Whiting 1 is the second closest GC to the plane containing the orbit of Sgr, after M 54.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Among the most likely members, only NGC 5634 and Whiting 1 are far away from the Sgr core and both are associated with the trailing arm in the LM10 model. Although no underlying population was found at a compatible distance around NGC 5634 in CB14, the abundances derived by Sbordone et al (2015) for this cluster are consistent with those of the main body of Sgr. Law & Majewski (2010a) also show that Whiting 1 is the second closest GC to the plane containing the orbit of Sgr, after M 54.…”
Section: Resultsmentioning
confidence: 51%
“…Indeed, four GCs are immersed in the Sgr main body (M 54, Arp 2, Terzan 7 and Terzan 8; Da Costa & Armandroff 1995) and multiple Galactic halo GCs have been associated with the accreted galaxy (e.g. Dinescu et al 2000;Bellazzini et al 2002;Palma et al 2002;Martínez-Delgado et al 2002;Bellazzini et al 2003;Carraro 2009;Forbes & Bridges 2010;Dotter et al 2011;Sbordone et al 2015). The total number of GCs likely associated with Sgr may reach ∼ 20% of the outer halo GC population at R G > 10 kpc (Bellazzini et al 2003), and Law & Majewski (2010a) found 9 globulars compatible with the orbit of the stream predicted by their model (Law & Majewski 2010b, hereafter LM10).…”
Section: Introductionmentioning
confidence: 99%
“…1, lower panel. We converted the x,y positions given in the catalogue to RA and Dec using stars in the Two Micron All Sky Survey (2MASS, Skrutskie et al 2006) for the astrometric conversion and the code cataxcorr, developed by Paolo Montegriffo at the INAF -Osservatorio Astronomico di Bologna 1 . We then selected stars on the red giant branch (RGB) and asymptotic giant branch (AGB) and allocated targets using the ESO positioner fposs.…”
Section: Observations and Analysismentioning
confidence: 99%
“…We retrieved the 2MASS magnitudes (Skrutskie et al 2006) of the 43 RV-member stars; K magnitudes, 2MASS identification and quality flag are given in Table 2. Following our well tested procedure (for a detailed description, see Carretta et al 2009a,b), effective temperatures T eff were derived using an average relation between apparent magnitudes and first-pass temperatures from V − K colours and the calibrations of Alonso et al (1999Alonso et al ( , 2001.…”
Section: Atmospheric Parametersmentioning
confidence: 99%
“…In the case of Sgr, at least 4 globulars are found in its main body E-mail: jcarballo@astro.puc.cl (M 54, Arp 2, Terzan 7 and Terzan 8; Da Costa & Armandroff 1995) and a few halo GCs have been associated with the stream across the sky (e.g. Dinescu et al 2000;Bellazzini et al 2002;Palma et al 2002;Martínez-Delgado et al 2002;Bellazzini et al 2003;Carraro 2009;Forbes & Bridges 2010;Dotter et al 2011;Sbordone et al 2015). Bellazzini et al (2003) estimated that ∼ 20% of halo GCs beyond R G = 10 kpc might be clusters formed in the interior of Sgr and later accreted by our Galaxy, while Law & Majewski (2010a, hereafter LM10a) proposed a list of 9 of these systems spatially and kinematically compatible with the predicted path of the stream (Law & Majewski 2010b, hereafter LM10b).…”
Section: Introductionmentioning
confidence: 99%